ҚАРАҚАЛПАҚ ӘДЕБИЯТТАНЫЎ ИЛИМИНДЕ ЛИРИКАЛЫҚ СУБЪЕКТТИӉ ИЗЕРТЛЕНИЎ МӘСЕЛЕЛЕРИ - Дабылов, П. (FAN va JAMIYAT, 2023)
In the article, the issue of studying the problem of the lyrical subject in Karakalpak literary criticism is studied in the historical and evolutionary aspect. A reaction is given to the scientific views of Karakalpak literary critics on lyrical themes. Different aspects of the character of the lyrical hero and the author are revealed. As a result, the questions of the lyrical hero and the lyrical subject are substantiated from a scientific point of view.